Exogenous factors of rhythmic gymnastics development in modern conditions - Morozova L. V.; Bystrova I. V.; Ponimasov O. E. (Theory and Practice of Physical Culture, 2023)
Objective of the study is the methodological substantiation of external factors of influence that determine the direction of the pedagogical algorithms of the training process in rhythmic gymnastics at the present stage of sports development.